On the problem of ventilation control in case of a tunnel fire event - Sturm, Peter; Beyer, Michael; Rafiei, Mehdi (Case studies in fire safety, 2017)
•Correct ventilation of a tunnel during a fire event is of utmost importance.•Various philosophies for such a ‘fire ventilation’ exist, some of them have pros and cons, some have to be avoided.•Ventilation control for critical velocity might be not appropriate in case of fires in congested traffic.•Short detection and ventilation response times are vital for ventilation during the self-rescue phase.•High quality air velocity sensors and correct placement of these sensors are of utmost importance.•Case studies from two long Alpine tunnels show that various options for smoke management are available. The proper operation of a ventilation system plays a key role in tunnel safety. Foremost, the ventilation system needs to provide acceptable air quality for the safe passage of tunnel users. Further, it needs to provide tenable environment and to facilitate rescue conditions during a smoke or fire event. While accomplishing the first task (normal operation), i.e. providing sufficient fresh air, is relatively straightforward, dealing with the second issue is the subject of considerable debate since defining the best means to ventilate a tunnel during a fire emergency is not always clear. Although fire tests in tunnels have been performed since the early 1960s, and although the topic of fire ventilation was raised in early national and international guidelines, relatively little interest was given to fire ventilation until several big fire events occurred in the 1990s. The tunnel ventilation systems and ventilation methodologies existing at that time proved to work well under normal operation, but failed during fire ventilation. Nowadays, the design and operation of the ventilation system during fire incidents (commonly called ‘fire ventilation’) is a major topic. While the design might follow the well-established principles, the question, ‘how to control tunnel ventilation during a fire event?’, is quite controversial. This paper discusses methods of fire ventilation with a focus on the methodologies themselves as well as on the requirements for sensors and control technologies.